2008
DOI: 10.1038/jid.2008.117
|View full text |Cite|
|
Sign up to set email alerts
|

Antibodies Elicited by Inactivated Propionibacterium acnes-Based Vaccines Exert Protective Immunity and Attenuate the IL-8 Production in Human Sebocytes: Relevance to Therapy for Acne Vulgaris

Abstract: Propionibacterium acnes is a key pathogen involved in the progression of inflammation in acne vulgaris. We examined whether vaccination against P. acnes suppressed P. acnes-induced skin inflammation. Inactivation of P. acnes with heat was employed to create a P. acnes-based vaccine. Intranasal immunization in mice with this inactivated vaccine provoked specific antibodies against P. acnes. Most notably, immunization with inactivated vaccines generated in vivo protective immunity against P. acnes challenge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 49 publications
0
60
1
6
Order By: Relevance
“…It has recently been shown that the antibodies elicited by inactivated P. acnes in intranasally immunized mice decrease IL-8 production, thereby decreasing inflammation and improving clinical signs [32]. We therefore hypothesized that the antiinflammatory effects of nicotinamide might be at least partly due to the ability of this molecule to regulate IL-8 production in our model based on keratinocytes stimulated by P. acnes.…”
Section: Discussionmentioning
confidence: 96%
“…It has recently been shown that the antibodies elicited by inactivated P. acnes in intranasally immunized mice decrease IL-8 production, thereby decreasing inflammation and improving clinical signs [32]. We therefore hypothesized that the antiinflammatory effects of nicotinamide might be at least partly due to the ability of this molecule to regulate IL-8 production in our model based on keratinocytes stimulated by P. acnes.…”
Section: Discussionmentioning
confidence: 96%
“…The pathogenetic role of IL-8 has been postulated, at least in part, in neutrophil-related skin diseases such as psoriasis [49,50], palmoplantar pustulosis [50] and acne [48,51,52]. Propionibacterium acnes is feasible for inducing IL-8 production in various cell types including NHEKs [52,53].…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
“…IL-8 is one of the major cyto/chemokines in inflammatory response and activates the recruitment and function of neutrophils [48]. The pathogenetic role of IL-8 has been postulated, at least in part, in neutrophil-related skin diseases such as psoriasis [49,50], palmoplantar pustulosis [50] and acne [48,51,52].…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
“…The pathogenesis of this disease is complex, involving sebaceous gland hypertrophy, increased seborrhea with the presence of oxidized lipids, pilosebaceous duct hyperkeratinization, and colonization with Propionibacterium acnes, resulting in perifollicular inflammation (2,3). Among various mediators orchestrating the inflammatory response of the pilosebaceous unit in acne, several cytokines, including IL-1, IL-6, IL-8, and TNF-a, have been implicated (4)(5)(6)(7)(8). In particular, IL-1 appears to play a key role in the pathogenesis of acne.…”
mentioning
confidence: 99%